Project-based learning with interactive video media to improve students' HOTS - Wibowo, Setyo Ajie; Nuro, Falistya Roisatul Mar'atin; Lestari, Dwi Nastiti (Universitas Kanjuruhan Malang, 2024)
This study aims to improve students' higher order thinking skills (HOTS) through the use of interactive video learning media in project-based learning at SDN Junrejo 2, Batu City. This class action research was conducted in two cycles, the research shows that interactive video facilitates the delivery of information so that in its application it makes it easier for students to understand the material. The importance of the role of educators in providing guidance and support was revealed in helping students in the course of learning and developing higher order thinking skills. The process of improving HOTS requires time, adaptation to the new learning model, and continuous mentoring. With the right strategy, the use of technology in learning can bring positive changes in the quality of education.